Prevalence of Helicobacter pylori infection in Fortaleza, Northeastern Brazil - Rodrigues, Maria N; Queiroz, Dulciene M M; Rodrigues, Rodrigo T; Rocha, Andreia M C; Luz, Carlos R L; Braga, Lucia L B C (Revista de Saúde Pública, 2005)
The prevalence of Helicobacter pylori infection was assessed in a randomly selected sample of individuals from low-income community in Fortaleza, Northeastern Brazil. Overall, 384 out of 610 participants (62.9%) were H. pylori positive. A 47.5% infection rate was found in subjects aged six months to 10 years old, increased to 73.3% in subjects aged 11-20 years and then continued to increase with age reaching up to 87% in those over 60 years old. After this age group, the prevalence decreased slightly. The prevalence of infection increased significantly with age (p